2018
DOI: 10.1111/jcmm.14113
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned medium from amniotic cells protects striatal degeneration and ameliorates motor deficits in the R6/2 mouse model of Huntington's disease

Abstract: Inflammation significantly impacts the progression of Huntington's disease (HD) and the mutant HTT protein determines a pro‐inflammatory activation of microglia. Mesenchymal stem/stromal cells (MSC) from the amniotic membrane (hAMSC), and their conditioned medium (CM‐hAMSC), have been shown to possess protective effects in vitro and in vivo in animal models of immune‐based disorders and of traumatic brain injury, which have been shown to be mediated by their immunomodulatory properties.In this study, in the R6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 66 publications
0
38
0
Order By: Relevance
“…Moreover, and most importantly, it is rich in stromal cells (hAMSCs) with immunomodulatory and regenerative properties [10]. Due to these features, in different preclinical inflammatory disease models, hAMSCs and their conditioned medium (CM-hAMSC) have been successfully exploited, including for lung [11][12][13][14] and liver fibrosis [15], wound healing [16][17][18], collagen-induced arthritis [19,20], multiple sclerosis [19], inflammatory bowel disease, colitis [21], sepsis [19], traumatic brain injury [22], and Huntington's disease [23]. Accordingly, in vitro, we and others have demonstrated that hAMSCs and CM-hAMSC suppress the proliferation, inflammatory cytokine production, and functions of T lymphocytes [24,25], monocytes [18], dendritic cells [26], macrophages [18], and natural killer cells [27], while inducing a phenotype and functional switch of monocytes toward macrophages with anti-inflammatory pro-regenerative M2-like features [18,25], supporting the expansions of regulatory T cells [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, and most importantly, it is rich in stromal cells (hAMSCs) with immunomodulatory and regenerative properties [10]. Due to these features, in different preclinical inflammatory disease models, hAMSCs and their conditioned medium (CM-hAMSC) have been successfully exploited, including for lung [11][12][13][14] and liver fibrosis [15], wound healing [16][17][18], collagen-induced arthritis [19,20], multiple sclerosis [19], inflammatory bowel disease, colitis [21], sepsis [19], traumatic brain injury [22], and Huntington's disease [23]. Accordingly, in vitro, we and others have demonstrated that hAMSCs and CM-hAMSC suppress the proliferation, inflammatory cytokine production, and functions of T lymphocytes [24,25], monocytes [18], dendritic cells [26], macrophages [18], and natural killer cells [27], while inducing a phenotype and functional switch of monocytes toward macrophages with anti-inflammatory pro-regenerative M2-like features [18,25], supporting the expansions of regulatory T cells [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…These capacities have been linked to the release of molecules like indoleamine 2,3-dioxygenase (IDO), prostaglandin E2, interleukin-10 (IL-10), human leukocyte antigen-G, TGF-β, and HGF (Dorronsoro et al, 2013 ). It has been demonstrated that the systemic administration of CM derived from amniotic membrane MSC ameliorates motor dysfunctions, brain pathology, and decreased microglial activation in HD animal model (Giampà et al, 2019 ).…”
Section: Cellular-free Approachesmentioning
confidence: 99%
“…Tremendous treatment options have been attempted to treat TBI, among which stem cell replacement therapy is considered as a promising way to regenerate brain tissue [ 5 ]. Human amniotic mesenchymal stromal cells (hAMSCs) have attracted much attention since they are easily obtained without minimal ethical controversy [ 6 , 7 ]. Francesca et al have found that hAMSCs showed neuronal rescue and introduction of trophic factors in TBI, which are favorable to protect brain [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Francesca et al have found that hAMSCs showed neuronal rescue and introduction of trophic factors in TBI, which are favorable to protect brain [ 8 ]. Other researchers have found that hAMSCs treated-TBI present a significant decrease of microglia activation [ 6 ], as well as upregulation of vascular endothelial growth factor (VEGF) and brain-derived neurotrophic factor (BDNF) [ 9 ]. These results indicate that hAMSCs have great potential to protect the injured brain, reduce the loss of neurons, increase the expression of nutritional factors, and partially restore brain function.…”
Section: Introductionmentioning
confidence: 99%